2018
DOI: 10.1038/s41598-017-19063-6
|View full text |Cite
|
Sign up to set email alerts
|

Prime-boost vaccination with recombinant protein and adenovirus-vector expressing Plasmodium vivax circumsporozoite protein (CSP) partially protects mice against Pb/Pv sporozoite challenge

Abstract: Vaccine development against Plasmodium vivax malaria lags behind that for Plasmodium falciparum. To narrow this gap, we administered recombinant antigens based on P. vivax circumsporozoite protein (CSP) to mice. We expressed in Pichia pastoris two chimeric proteins by merging the three central repeat regions of different CSP alleles (VK210, VK247, and P. vivax-like). The first construct (yPvCSP-AllFL) contained the fused repeat regions flanked by N- and C-terminal regions. The second construct (yPvCSP-AllCT) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 46 publications
4
37
1
Order By: Relevance
“…By eliciting an inflammatory Th1-like response in mice and humans, it was hypothesized that such a response could contribute to protection [50]. Previously, our research group showed that Poly (I:C) was responsible to enhance not only the immunogenicity of PvCSP recombinant proteins upon vaccination [21,33] but also protection after a parasitic challenge [22,41]. In this study, the NLP-CSP R vaccine formulation induced a predominance of IgG2c over IgG1.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…By eliciting an inflammatory Th1-like response in mice and humans, it was hypothesized that such a response could contribute to protection [50]. Previously, our research group showed that Poly (I:C) was responsible to enhance not only the immunogenicity of PvCSP recombinant proteins upon vaccination [21,33] but also protection after a parasitic challenge [22,41]. In this study, the NLP-CSP R vaccine formulation induced a predominance of IgG2c over IgG1.…”
Section: Discussionmentioning
confidence: 61%
“…One of the most effective ways to analyze vaccine efficacy is through a challenge test. This approach has been used previously and has proven effective at demonstrating vaccine-induced protection [21,22,41]. However, P. vivax does not infect rodents.…”
Section: Assessment Of Vaccine Efficacymentioning
confidence: 99%
“…Malaria elimination based on vaccines will require the development of a vaccine not only against P. falciparum, but also against P. vivax. Many research groups in Brazil and abroad are working on the development of a P. vivax vaccine based on the PvCSP antigen (9)(10)(11). However, it is reasonable to foresee, based on the results obtained with the clinical trials of RTS,S/AS01, that a P. vivax vaccine based only on the PvCSP may not be fully effective by itself.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of a continuous P. vivax laboratory culture has so far thwarted efficacy tests of these available vaccine formulations in pre-clinical studies, which is an obvious obstacle to progress with these formulations to clinical tests in humans. The mouse-infecting P. berghei has been used for efficacy tests of PvCSP-based formulations (10,11). These studies used P. berghei hybrid mutant lines expressing the PvCSP to challenge mice immunized with formulations based on the P. vivax antigen.…”
Section: Introductionmentioning
confidence: 99%
“…With the renewed interest in malaria eradication, the development of an effective malaria vaccine is high on the agenda. Diverse strategies are being proposed to develop better vaccines: identification of new vaccine candidate [116], combinations of different antigens targeting the same stage or different stages [117]; new delivery systems and prime-boost strategies using different modalities [118]; and new adjuvants to induce stronger and longer lasting efficient immune responses [119][120][121][122]. However, for all vaccine types described, the absence of validated surrogates of protection to help select and prioritize different vaccine formulations is a major roadblock, which should be given priority to accelerate vaccine testing.…”
Section: Discussionmentioning
confidence: 99%